British memory research: a journey through the 20th century. - Parkin, Alan J.; Hunkin, Nicola M. (British Journal of Psychology, 2001)
A century of research in memory has generated a wealth of knowledge encompassing theoretical developments within a number of distinct domains of memory. The aim of this article is to explore the progress made in memory research during the 20th century, to indicate critical influences on the direction of research, and to illustrate the important contribution made by British researchers. This article is confined to human memory research, and reviews research findings from the various psychological disciplines studied over the past 100 years. Reprinted by permission of the publisher.